The Analysis of Effect of Removing Pitcher Masses with Sanding Methode on Its Hydraulic Conductivity and Water Seepage Velocity on Ultisol Soil Surface - Raja Bagus Hariawan Agung; Achwil Putra Munir; Saipul Bahri Daulay (Jurnal Rekayasa Pangan dan Pertanian, 2015)
Pitchers that are made of clay loam and burnt with high temperature have ability to autoregulate soil irrigation which is an efficient technique among other system of irrigation. The Important physical characteristics of pitcher are hydraulic conductivity and porosity. This research was one of preliminary study in making regulation of pitcher physical characteristics using sanding methode. This research was performed using non factorial randomized block design. Parameters analyzed were porosity, hydraulic conductivity, water seepage volume and soil surface wetting distance. The result showed the sanding methode had no significant effect on porosity, hydraulic conductivity, water seepage volume and soil surface wetting distance. Key Word: conductivity, pitcher, porosity, hydraulic, sanding method, water seepage